1983
DOI: 10.3758/bf03205886
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile masking: Effects of oneand two-site stimulation

Abstract: Masked vibrotactile thresholds at the index fingertip were measured as a function of masker intensities, which were applied to the thenar eminence of the same hand. Test and masker frequencies were selected so that the Pacinian and non-Pacinian receptor systems were selectively activated. Remote-site masking was effective only when both masker and test stimulus were within the frequency range of the Pacinian system. Cross-channelmasking did not occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 50 publications
3
43
1
Order By: Relevance
“…However, vibrotactile masking and adaptation phenomena bear marked similarities to presentation-order effects. In vibrotactile masking, a prior stimulus may substantially raise the detection threshold of a target vibration occurring up to 200 msec later (Gescheider, Bolanowski & Verrillo, 1989;Gescheider, Bolanowski, Verrillo, Arpajian, & Ryan, 1990;Gescheider, Verrillo, & Van Doren, 1982;Hamer, Verrillo, & Zwislocki, 1983;Kirman, 1986;Verrillo & Gescheider, 1977;Verrillo, Gescheider, Calman, & Van Doren, 1983). However, masking effects completely dissipate 500 msec after stimulation, the shortest delay period used in the present study, whereas observed discrimination order effects persisted for 30-sec delays.…”
Section: Presentation-order Effectscontrasting
confidence: 50%
“…However, vibrotactile masking and adaptation phenomena bear marked similarities to presentation-order effects. In vibrotactile masking, a prior stimulus may substantially raise the detection threshold of a target vibration occurring up to 200 msec later (Gescheider, Bolanowski & Verrillo, 1989;Gescheider, Bolanowski, Verrillo, Arpajian, & Ryan, 1990;Gescheider, Verrillo, & Van Doren, 1982;Hamer, Verrillo, & Zwislocki, 1983;Kirman, 1986;Verrillo & Gescheider, 1977;Verrillo, Gescheider, Calman, & Van Doren, 1983). However, masking effects completely dissipate 500 msec after stimulation, the shortest delay period used in the present study, whereas observed discrimination order effects persisted for 30-sec delays.…”
Section: Presentation-order Effectscontrasting
confidence: 50%
“…For example, Sherrick ͑1964͒ reported an increase of almost 30 dB in the detection threshold for a 350-ms pulsed 150-Hz vibrotactile signal at the right index finger when presented simultaneously with a 350-ms pulsed 150-Hz vibrotactile masker of 30 dB SL at the right little finger. Verrillo et al ͑1983͒ observed substantial masking of a 300-ms, 300-Hz test stimulus at the index fingertip when it was temporally centered within a 730-ms, 300-Hz masking stimulus at the ipsilateral thenar eminence. They further measured vibration at the index fingertip due to physical transmission of masking vibration from the thenar site, and thereby established that even their maximum intensity masker produced only subthreshold vibration at the fingertip surface ͑suggesting that the underlying process is likely more central͒.…”
Section: B Tactual Temporal Order Discriminationmentioning
confidence: 99%
“…Cross-channel masking is often based on the assumption that Pacinian and non-Pacinian systems are independent in response: a masker stimulating one system should not alter the detectability of a signal in the other system (Labs et al, 1978;Hamer, 1979;Hamer et al, 1983;Gescheider et al, 1982;Verrillo et al, 1983). A horizontal line in a masking function implies independence in the detection response, as indicated by Hamer et al (1983):…”
Section: Cross-channel Maskingmentioning
confidence: 99%